FAKTOR-FAKTOR YANG MEMPENGARUHI SEMANGAT KERJA PEGAWAI - Syaiful Amri; Nurhidayati Nurhidayati; Rosiya Wardani (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to determine the effect of work environment, workload and compensation on morale partially and simultaneously. This type of research is associative research. Data collection techniques using observation, interviews and questionnaires. The population in this study are all employees in the Department of manpower and Transmigration as many as 75 employees. Sampling technique using non probability sampling with purposive sampling method, so that the number of samples obtained as many as 48 people. The data analysis technique used is multiple linear regression analysis. The results showed that environmental variables partially no significant effect on morale, while workload and compensation partially significant effect on morale. The variables work environment, workload and compensation simultaneously have a significant influence on morale. The results of this study were also able to show that the independent variables (work environment, workload and compensation) were able to explain the dependent variable (morale) by 44%. While the remaining 46% of morale is influenced by other variables outside the work environment, workload and compensation.